Associação entre úlcera falcêmica, inflamação e hemólise - Aragão, Matheus Todt (2022)
INTRODUCTION: Approximately 5% of the world population has genes that encode hemoglobinopathies, and it is estimated that more than 25 million people are affected by sickle cell anemia worldwide. Among these patients, musculoskeletal complica- tions are a frequent cause of morbidity, with sickle cell ulcers being the most com- mon, affecting up to 10% of patients with sickle cell anemia. The etiopathogenesis of these ulcers is complex, not being fully characterized yet. Given the scarcity of data on the subject, it is proposed to study the association between hemolysis, inflamma- tion and sickle cell ulcers. METHODOLOGY: This is a cross-sectional and analytical study involving patients with sickle cell anemia and a history of leg ulcers, which were compared to patients with sickle cell anemia without lesions. All patients involved were homozygous, and the groups were matched for age, presence of comorbidities and medication use. To avoid biases related to sickle cell disease activity, patients with a recent history of vasoocclusive crisis, hospital admission, blood transfusion and infectious or inflammatory diseases were excluded. The occurrence of ulcers, time of evolution, number of recurrences, hemolysis markers (hemoglobin, LDH and bilirubin) and pro and anti-inflammatory markers (IL-1b,6,8,10 and TNF-alpha) were evaluated. RESULTS: There was no statistically significant correlation between levels of hemolysis markers and cytokines (pro-inflammatory and anti-inflammatory), the emergence or evolution of sickle cell ulcers. It is suggested that both hemolysis and inflammation play secondary roles in a complex multifactorial mechanism, not config- uring essential conditions for the occurrence of lesions. CONCLUSION: A broader view of the pathophysiology of skin ulcers is proposed, giving greater emphasis to an association of systemic and local factors, and less relevance to laboratory markers.